1987
DOI: 10.1021/bi00395a020
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine and carboxyl protonation changes in the bacteriorhodopsin photocycle. 1. M412 and L550 intermediates

Abstract: The role of tyrosines in the bacteriorhodopsin (bR) photocycle has been investigated by using Fourier transform infrared (FTIR) and UV difference spectroscopies. Tyrosine contributions to the BR570----M412 FTIR difference spectra recorded at several temperatures and pH's were identified by isotopically labelling tyrosine residues in bacteriorhodopsin. The frequencies and deuterium/hydrogen exchange sensitivities of these peaks and of peaks in spectra of model compounds in several environments suggest that at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
102
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 49 publications
(66 reference statements)
17
102
3
Order By: Relevance
“…There is a decreased intensity near 1657 (Ϫ) cm Ϫ1 and an increase of the 1633 (Ϫ) cm Ϫ1 band, which is likely to reflect the expected downshift of the CϭN Schiff base stretching vibration assigned at 1650 cm Ϫ1 and 1627 cm Ϫ1 in H 2 O and D 2 O, respectively (38). Additional changes near 1618 (ϩ) cm Ϫ1 and 1600 (Ϫ) cm Ϫ1 may reflect the D 2 O induced downshift of a tyrosine ring mode near 1620 cm Ϫ1 as previously observed in bacteriorhodopsin (48). from the receptor are evident in this time series including: (i) the increased negative intensity near 1694 cm Ϫ1 (Asn/Gln or amide I); (ii) reduction in negative intensity near 1664 cm Ϫ1 (amide I); and (iii) reduction in intensity of negative band at 1545 cm Ϫ1 (ethylenic stretch of chromophore) along with the appearance of a shoulder at 1555 cm Ϫ1 , which might reflect the presence of the N intermediate.…”
Section: Conformational Changes In Srii-transducer Complexsupporting
confidence: 69%
“…There is a decreased intensity near 1657 (Ϫ) cm Ϫ1 and an increase of the 1633 (Ϫ) cm Ϫ1 band, which is likely to reflect the expected downshift of the CϭN Schiff base stretching vibration assigned at 1650 cm Ϫ1 and 1627 cm Ϫ1 in H 2 O and D 2 O, respectively (38). Additional changes near 1618 (ϩ) cm Ϫ1 and 1600 (Ϫ) cm Ϫ1 may reflect the D 2 O induced downshift of a tyrosine ring mode near 1620 cm Ϫ1 as previously observed in bacteriorhodopsin (48). from the receptor are evident in this time series including: (i) the increased negative intensity near 1694 cm Ϫ1 (Asn/Gln or amide I); (ii) reduction in negative intensity near 1664 cm Ϫ1 (amide I); and (iii) reduction in intensity of negative band at 1545 cm Ϫ1 (ethylenic stretch of chromophore) along with the appearance of a shoulder at 1555 cm Ϫ1 , which might reflect the presence of the N intermediate.…”
Section: Conformational Changes In Srii-transducer Complexsupporting
confidence: 69%
“…There is clearly an ample number of these residues for the formation of a membrane-spanning HBC, particularly when one recalls that a single HBC may be composed of residues from more than one transmembrane helix in the folded protein. Spectroscopic data have suggested that during the proton pumping photocycle of BR, protonation/ deprotonation events occur at several potential HBC residues, tyrosine and aspartate (15); environmental change also occurs about tryptophan residues (16). Most recently, Khorana and co-workers have expressed the www.annualreviews.org/aronline Annual Reviews gene for BR in E. coli and have begun systematic site-directed mutagenesis studies to identify the key amino acid residues required for proton pumping.…”
Section: Bacteriorhodopsinmentioning
confidence: 99%
“…This is a reversible first-order reaction (Bray & White, 1966). The rate equations are, .100 95 Roepe et al, 1987;Gerwert et al, 1989;Bousche et al, 1991;Braiman et al, 1991;Pfefferle et al, 1991). (Bell, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The Schiff base is deprotonated (Lewis et al, 1974). Infrared spectroscopy has provided information concerning the protonation states of carboxyi and tyrosine sidechains at distinct points in the photocycle (Engelhard et al, 1985;Rothschild et al, 1986;Dollinger et al, 1986;Roepe et al, 1987). FTIR spectroscopy demonstrates that both…”
Section: IIImentioning
confidence: 99%